2021
DOI: 10.1111/jora.12647
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Adjustment During COVID‐19: The Role of Close Relationships and COVID‐19‐related Stress

Abstract: During the COVID‐19 pandemic, adolescents’ typical social support systems have been disrupted. The present study examined adolescent adjustment during the pandemic (summer, 2020) while controlling for pre‐pandemic adjustment (2017–2018) in 170 youth (ages 12–20) from Missouri and Florida. We also examined whether positive and negative relationship qualities with four close others (i.e., mothers, fathers, siblings, and best friends) interacted with COVID‐related stress to impact adolescent adjustment. In genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 59 publications
3
56
1
Order By: Relevance
“…However, Campione‐Barr et al. ( 2021 ) showed that relationships with best friends and siblings were more significantly impacted by COVID‐related stress than those with parents. Further research is needed to understand the potential protective role of siblings for adolescents in times of crisis.…”
Section: Introductionmentioning
confidence: 99%
“…However, Campione‐Barr et al. ( 2021 ) showed that relationships with best friends and siblings were more significantly impacted by COVID‐related stress than those with parents. Further research is needed to understand the potential protective role of siblings for adolescents in times of crisis.…”
Section: Introductionmentioning
confidence: 99%
“…However, they didn’t find such a moderating effect, whereas pre-COVID support from friends predicted having less COVID-related stress. In contrast, Campione-Barr et al (2021) , demonstrated that close relationships to best friends predicted adolescents’ ability to adjust to pandemic-related concerns (i.e., by showing lower levels of anxiety, depressive symptoms, problem behavior) while controlling for their pre-pandemic adjustment.…”
Section: Introductionmentioning
confidence: 87%
“…Based on these assumptions and relying on pre-pandemic and general literature about social support as well as based on recent literature examining social support during the pandemic (e.g., Ellis et al, 2020 ; Szkody et al, 2020 ; Campione-Barr et al, 2021 ; Bernasco et al, 2021 ; Ye et al, 2021 ), we expected that adolescents who perceived higher levels of social support during COVID-19 related school closures would report better mental health. Moreover, we investigated whether perceived social support buffered negative associations between educational and health concerns and mental health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, internalizing problems before the pandemic were also found to be predictive of less friend support during the pandemic (Bernasco et al., 2021 ), suggesting that it is easier for adolescents with higher levels of adjustment to maintain their friendships when this is challenged by circumstances. Moreover, friendships can also increase the negative impact of the pandemic: For best friends, higher relationship positivity in the context of high levels of COVID‐related stress was associated with greater adolescent problem behavior (Campione‐Barr et al., 2021 ), which might be attributed to peer deviancy training processes.…”
Section: Social Connection During the Pandemicmentioning
confidence: 99%